Growth of free-standing bulk wurtzite AlxGa1−xN layers by molecular beam epitaxy using a highly efficient RF plasma source - Novikov, Sergei V.; Staddon, Christopher R.; Sahonta, S-L; Oliver, R.A.; Humphreys, C.J.; Foxon, C.T. (Elsevier, 2016)
The recent development of group III nitrides allows researchers world-wide to consider AlGaN based light emitting diodes as a possible new alternative deep ultra–violet light source for surface decontamination and water purification. In this paper we will describe our recent results on plasma-assisted molecular beam epitaxy (PA-MBE) growth of free-standing wurtzite AlxGa1−xN bulk crystals using the latest model of Riber's highly efficient nitrogen RF plasma source. We have achieved AlGaN growth rates up to 3 µm/h. Wurtzite AlxGa1−xN layers with thicknesses up to 100 μm were successfully grown by PA-MBE on 2-inch and 3-inch GaAs (111)B substrates. After growth the GaAs was subsequently removed using a chemical etch to achieve free-standing AlxGa1−xN wafers. Free-standing bulk AlxGa1−xN wafers with thicknesses in the range 30–100 μm may be used as substrates for further growth of AlxGa1−xN-based structures and devices. High Resolution Scanning Transmission Electron Microscopy (HR-STEM) and Convergent Beam Electron Diffraction (CBED) were employed for detailed structural analysis of AlGaN/GaAs (111)B interface and allowed us to determine the N-polarity of AlGaN layers grown on GaAs (111)B substrates. The novel, high efficiency RF plasma source allowed us to achieve free-standing AlxGa1−xN layers in a single day's growth, making this a commercially viable process.